Blended Poe AI-Human Teaching: AI Sebagai Mitra Pedagogis Guru dalam Praktik Pembelajaran - Azhari, Jalaludin; Moh. Isbir; Binti Nur Afifah; Machbub Ainurrofiq (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The study of this research aims to examine how the Arabic language practice in MA Al-Falah Tlanakan has changed through the integration of Poe AI as a pedagogical partner, which includes the design of implementation, the impact on students on the affective side, and the design of a learning reconstruction model. Qualitative phenomenology is used in this research with observation, in-depth interviews and documentation as a tool to collect data. Participants in collecting data consisted of school principals, maple teachers and students. The findings in the field show that the integration of Poe AI is systematically planned through three stages, namely technical guidance for teachers, revitalization and optimization of digital infrastructure facilities (rooter, lab, computer and language) and adjustment of Teaching Modules. The results of the integration can be shown through the application of digital muhadastah, AI-based kitabah and insha', as well as Qira'ah Interactive, which actually forms a safe learning space that is able to reduce language anxiety and increase independent learning outside the classroom. The results of this research propose a Blended Poe AI–Human Teaching (BPHT) model that positions Poe AI as a complementary pedagogical tool, not a replacement for the role of teachers